Investigation of Novel Composite Materials for Thermochemical Heat Storage Systems - Salih Cem Akcaoglu; Zhifa Sun; Stephen Carl Moratti; Georgios Martinopoulos (Energies, 2020)
Increasing energy prices make space heating more expensive every year in The Organisation for Economic Co-operation and Development (OECD) member countries. Thermochemical heat storage systems (THSS) can be used to reduce residential energy consumption for space heating and to control humidity. Utilizing compressed thermochemical pellets as heat storage materials is a way to increase volumetric energy storage capacity and to improve the performance of the THSS. In this work, expanded natural graphite (ENG), activated carbon (AC), strontium bromide, and magnesium sulphate were mixed in different mass ratios and compressed under applied pressures in a range of 0.77 to 5.2 kN⋅mm−2 to form composite pellets with a diameter of 12 and 25 mm, respectively, and a thickness from 1.5 to 25 mm. These pellets were characterized using thermogravimetric analysis and differential scanning calorimetry. Cyclic tests of hydration at 20 °C and dehydration at 85 °C were conducted to investigate changes in the surface morphology and the heat and mass transfer characteristics of the composite pellets. The permeability and thermal conductivity of the composite pellets were also measured. It was found that the structural stability of the pellets was enhanced by increasing the compression pressure. Utilizing AC and ENG in the composite mixture enhanced the porosity, thermal conductivity, and the permeability of the pellets.